2015
DOI: 10.1111/gcb.12825
|View full text |Cite
|
Sign up to set email alerts
|

A landscape ecology approach identifies important drivers of urban biodiversity

Abstract: Cities are growing rapidly worldwide, yet a mechanistic understanding of the impact of urbanization on biodiversity is lacking. We assessed the impact of urbanization on arthropod diversity (species richness and evenness) and abundance in a study of six cities and nearby intensively managed agricultural areas. Within the urban ecosystem, we disentangled the relative importance of two key landscape factors affecting biodiversity, namely the amount of vegetated area and patch isolation. To do so, we a priori sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
70
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 134 publications
(79 citation statements)
references
References 72 publications
1
70
1
3
Order By: Relevance
“…One location was visited only six times (n = 110). We recorded a total of 3,404 hoverflies (2,710 migratory, 673 non-migratory and 21 unidentified individuals) 2012;Knop, 2016;Magura et al, 2010;Turrini & Knop, 2015). In contrast, these results are in disagreement with the studies ofBates et al (2011) andVerboven, Uyttenbroeck, Brys, and Hermy (2014) who reported a significant difference and a trend for a difference in hoverfly species richness between urban and rural landscapes.…”
contrasting
confidence: 62%
See 1 more Smart Citation
“…One location was visited only six times (n = 110). We recorded a total of 3,404 hoverflies (2,710 migratory, 673 non-migratory and 21 unidentified individuals) 2012;Knop, 2016;Magura et al, 2010;Turrini & Knop, 2015). In contrast, these results are in disagreement with the studies ofBates et al (2011) andVerboven, Uyttenbroeck, Brys, and Hermy (2014) who reported a significant difference and a trend for a difference in hoverfly species richness between urban and rural landscapes.…”
contrasting
confidence: 62%
“…While the negative effects of agricultural intensification on biodiversity are well known (e.g., Kleijn et al, 2009;Tscharntke, Klein, Kruess, Steffan-Dewenter, & Thies, 2005), the nature of the impact of urbanization remains relatively unclear (Faeth, Bang, & Saari, 2011;Mckinney, 2008). Previous research comparing urbanized areas to rural areas has found contrasting effects of urbanization on species richness and diversity across taxa (e.g., Baldock et al, 2015;Faeth et al, 2011;Magura, Lövei, & Tóthmérész, 2010;Mckinney, 2008;Turrini & Knop, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, urbanization did not seem to have an overall negative impact, but it affected urbanization winners and losers in different ways as suggested by previous studies (e.g., Banaszak-Cibicka & Żmihorski, 2012; Hülsmann et al, 2015). Correspondingly, Turrini & Knop (2015) found that urbanization also favors specific species. Community composition may be determined by stochasticity (Sattler et al, 2010), and urbanization impacts depend on geographical, historical and economic factors of cities (McKinney, 2008).…”
Section: Discussionmentioning
confidence: 95%
“…Several studies have shown that urbanization promotes the reduction of diversity, but increases the abundance of so-called urban exploiters, species specialized in the urban environment (McKinney, 2008;Faeth et al, 2011;Aronson et al, 2014;Turrini and Knop, 2015). A consequence of this process is the biotic homogenization induced mostly because the few adapted species to urban areas become increasingly widespread and locally abundant in cities across the planet (McKinney, 2006).…”
Section: Discussionmentioning
confidence: 99%